Can Non-invasive Ventilation Modulate Cerebral, Respiratory, and Peripheral Muscle Oxygenation During High-Intensity Exercise in Patients With COPD-HF? - Goulart, Cássia da Luz; Caruso, Flávia Rossi; de Araújo, Adriana Sanches Garcia; Moura, Sílvia Cristina Garcia de; Catai, Aparecida Maria; Agostoni, Piergiuseppe; Mendes, Renata Gonçalves; Arena, Ross; Borghi-Silva, Audrey (Frontiers in Cardiovascular Medicine, 2022)
Aim: To evaluate the effect of non-invasive positive pressure ventilation (NIPPV) on: 1) metabolic, ventilatory, and hemodynamic responses; and 2) cerebral (Cox), respiratory and peripheral oxygenation when compared to SHAM ventilation during high-intensity exercise in patients with coexisting chronic obstructive pulmonary disease (COPD) and heart failure (HF). Methods and Results: On separate days, patients performed incremental cardiopulmonary exercise testing and two constant-work rate tests receiving NIPPV or SHAM (bilevel mode - Astral 150) in a random order until the limit of tolerance (Tlim). During exercise, oxyhemoglobin (O2Hb) and deoxyhemoglobin (HHb) were assessed using near-infrared spectroscopy (Oxymon, Artinis Medical Systems, Einsteinweg, Netherland). NIPPV associated with high-intensity exercise caused a significant increase in exercise tolerance, peak oxygen consumption (V̇O2 in mlO2•kg-1•min-1), minute ventilation peak (V̇E inmL/min), SpO2 (%), and lactate/tlim (mmol/s) when compared with SHAM ventilation. In cerebral, respiratory and peripheral muscles, NIPPV resulted in a lower drop in [O2Hb] (p<0.05) and an improved deoxygenation response [HHb] (p<0.05) from the half of the test (60% of Tlim) when compared to SHAM ventilation. Conclusion: NIPPV during constant work-rate exercise led to provide respiratory muscle unloading with greater oxygen supply to the peripheral muscles, reducing muscle fatigue and sustaining longer exercise time in patients with COPD-HF.